Irish and Scottish Encounters with Indigenous Peoples : Canada, the United States, New Zealand, and Australia - Wilson, David A., 1950-; Morton, Graeme (McGill-Queen's University Press, 2013)
The expansion of the British Empire during the eighteenth and nineteenth centuries created the greatest mass migration in human history, in which the Irish and Scots played a central, complex, and controversial role. The essays in this volume explore the diverse encounters Irish and Scottish migrants had with Indigenous peoples in North America and Australasia. The Irish and Scots were among the most active and enthusiastic participants in what one contributor describes as 'the greatest single period of land theft, cultural pillage, and casual genocide in world history'.